2008
DOI: 10.1016/j.virol.2008.04.021
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus infection of Drosophila melanogaster induces a protective RNAi response

Abstract: To determine if West Nile virus (WNV) infection of insect cells induces a protective RNAi response, Drosophila melanogaster S2 and Aedes albopictus C6/36 cells were infected with WNV, and the production of WNV-homologous small RNAs was assayed as an indicator of RNAi induction. A distinct population of approximately 25 nt WNV-homologous small RNAs was detected in infected S2 cells but not C6/36 cells. RNAi knockdown of Argonaute 2 in S2 cells resulted in slightly increased susceptibility to WNV infection, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
120
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 92 publications
6
120
1
Order By: Relevance
“…Using this approach, we were able to achieve ϳ80% suppression of each gene. One-step growth curve analysis of WNV (derived from infectious clone NY99 [23]) following a triple treatment of dsRNA (16 h prior to infection, 1 h postinfection, and 3 days postinfection [dpi]) revealed no significant difference in WNV titers between the dsDcr2 and dsAgo2 and the dsLuc control group, consistent with previously published findings (20). Conversely, when WNV-specific dsRNA was administered to the cells, WNV titers were significantly reduced at early time points but eventually rebounded to control-treated levels by 6 dpi (data not shown).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Using this approach, we were able to achieve ϳ80% suppression of each gene. One-step growth curve analysis of WNV (derived from infectious clone NY99 [23]) following a triple treatment of dsRNA (16 h prior to infection, 1 h postinfection, and 3 days postinfection [dpi]) revealed no significant difference in WNV titers between the dsDcr2 and dsAgo2 and the dsLuc control group, consistent with previously published findings (20). Conversely, when WNV-specific dsRNA was administered to the cells, WNV titers were significantly reduced at early time points but eventually rebounded to control-treated levels by 6 dpi (data not shown).…”
supporting
confidence: 89%
“…To accomplish this, Drosophila S2 cells were treated with a control double-stranded RNA (dsRNA), dsLuc, a dsRNA specific for one of two major components of the exo-siRNA pathway, Dicer-2 (dsDcr2) and Argonaute-2 (dsAgo2), or with anti-WNV dsRNA (dsRNA directed to the same region of the genome as the sequencing amplicons), using the soaking method (Tables 1 and 2) (19)(20)(21)(22). Using this approach, we were able to achieve ϳ80% suppression of each gene.…”
mentioning
confidence: 99%
“…Indeed, Flamenco has been proposed as an ovarian somatic sheet cells-only piRNA cluster, and as such validates the sensitivity of our deep-sequencing methodology. Before vpiRNAs were described, Zambon et al (10) and Chotkowski et al (37) reported that Piwi and Aub mutant flies were more sensitive to DXV and WNV infection, displaying an accelerated death and higher viral loads compared with WT flies. The fact that we did not observe the same phenotype in flies that are backcrossed leads us to believe that their observation is based on a genetic background effect.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies published before the discovery of vpiRNA highlighted a functional link between piRNA pathway and antiviral defense in flies. Piwi mutant flies were found to be more susceptible to both DXV and West Nile virus [WNV; (+)ssRNA, Flaviviridae] infections, and Aub mutant flies were found to be more susceptible to DXV (10,37).…”
Section: Significancementioning
confidence: 99%
“…RNAi is also functional in various mosquito cell lines (1,8,43,49,52). In the absence of RNAi, alphavirus and flavivirus replication and/or dissemination is enhanced in both mosquitoes and Drosophila (14,17,31,45,72). RNAi inhibitors weakly enhance SFV replicon replication in tick and mosquito cells (5,33), posing the questions of how, when, and where RNAi interferes with alphavirus infection in mosquito cells.…”
mentioning
confidence: 99%